2015
DOI: 10.4103/0377-4929.168879
|View full text |Cite
|
Sign up to set email alerts
|

Mixed adenoneuroendocrine carcinoma of the gallbladder, histopathological features

Abstract: An unusual case of mixed adenoneuroendocrine carcinoma is described which posed a diagnostic challenge in view of neuroendocrine component mimicking signet ring cells of adenocarcinoma. Diagnostic criteria for these mixed tumors, their histogenesis and treatment modalities are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Included studies. A total of 15 studies (14 case reports and 1 case series), which comprised 19 patients who successfully underwent surgical treatment for gMANEC were considered eligible for inclusion and analysis in our systematic review as shown in Table I (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies. A total of 15 studies (14 case reports and 1 case series), which comprised 19 patients who successfully underwent surgical treatment for gMANEC were considered eligible for inclusion and analysis in our systematic review as shown in Table I (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…A peculiar histomorphological finding in our case was the presence of an insular pattern of growth with peripheral palisading and salt-and-pepper nuclei. This component constituted almost half of the tumor, which was morphologically suggestive of mixed adenoneuroendocrine carcinoma [19]. Interestingly, these foci were negative for synaptophysin, chromogranin, NSE and CD56, while they were positive for cytokeratin, so mixed adenoneuroendocrine carcinoma was excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Other initial reports showed that biliary tract NETs are only 0.2–2.0% of bile duct neoplasm [9] , [10] , with reports of MANECs of the bile duct being scarce. There were reports of some bile duct MANECs since 2010, with their origins subdivided into the gallbladder [3] , [4] , [6] , [11] , [12] . This study is the first reported case of cystic duct MANEC.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroendocrine tumors (NETs) commonly occur in the gastrointestinal tract, pancreas, and lung, but bile duct origin of NETs is uncommon [2] . Some cases of MANEC derived from the bile duct have been reported [3] , [4] , [5] , [6] . Although NECs of the bile duct are frequently associated with liver or lymph node metastases in the preoperative state, aggressive radical operative therapy and adjuvant chemotherapy contributes to long-term outcomes [7] .…”
Section: Introductionmentioning
confidence: 99%